Changes in physical activity, diet, and body weight across the education and employment transitions of early adulthood: A systematic review and meta‐analysis. (19th January 2020) - Winpenny, Eleanor M.; Smith, Miranda; Penney, Tarra; Foubister, Campbell; Guagliano, Justin M.; Love, Rebecca; Clifford Astbury, Chloe; van Sluijs, Esther M.F.; Corder, Kirsten
Summary: Early adulthood is a time when individuals go through important life transitions, such as moving from high school into higher education or employment, but the impact of these life transitions on changes in body weight, diet, and physical activity is not known. We searched six electronic databases to July 2019 for longitudinal observational studies providing data on adiposity, diet, and/or physical activity across education or employment transitions in young people aged between 15 and 35 years. We found 19 studies, of which 17 assessed changes in physical activity, three body weight, and five diet or eating behaviours. Meta‐analysis (n=9) found that leaving high school was associated with a decrease of −7.04 (95% CI, −11.26, −2.82) min/day of moderate‐to‐vigorous physical activity. Three studies reported increases in body weight on leaving high school. A small number of studies suggested decreases in diet quality on leaving high school (n=2/4 papers) and leaving university (n=1) but not on starting employment (n=1). Studies suggested no change in physical activity on leaving university (n=4) but decreases in physical activity on starting employment (n=2/3). The transition of leaving high school is an important time to support individuals to prevent decreases in physical activity and gains in body weight.